Associations of Infant Subcutaneous Fat Mass with Total and Abdominal Fat Mass at School-Age: The Generation R Study - Santos, S (2016)
BACKGROUND:Skinfold thickness enables the measurement of overall and regional subcutaneous fatness in infancy and may be associated with total and abdominal body fat in later childhood. We examined the associations of subcutaneous fat in infancy with total and abdominal fat at school-age. METHODS:In a population-based prospective cohort study among 821 children, we calculated total subcutaneous fat (sum of biceps, triceps, suprailiacal, and subscapular skinfold thicknesses) and central-to-total subcutaneous fat ratio (sum of suprailiacal and subscapular skinfold thicknesses/total subcutaneous fat) at 1.5 and 24 months. At 6 years, we measured fat mass index (total fat/height(3) ), central-to-total fat ratio (trunk fat/total fat), and android-to-gynoid fat ratio (android fat/gynoid fat) by dual-energy X-ray absorptiometry and preperitoneal fat mass area by abdominal ultrasound. RESULTS:Central-to-total subcutaneous fat ratio at 1.5 months was positively associated with fat mass index and central-to-total fat ratio at 6 years, whereas both total and central-to-total subcutaneous fat ratio at 24 months were positively associated with all childhood adiposity measures. A 1-standard-deviation scores higher total subcutaneous fat at 24 months was associated with an increased risk of childhood overweight (odds ratio 1.70, 95% confidence interval 1.36, 2.12). These associations were weaker than those for body mass index and stronger among girls than boys. CONCLUSIONS:Subcutaneous fat in infancy is positively associated with total and abdominal fat at school-age. Our results also suggest that skinfold thicknesses add little value to estimate later body fat, as compared with body mass index.